The implementation of spatial information system to improve wells data integrity in pt Pertamina ep - Purwana, Hadi; Hanafi, Muhammad (The Indonesian Journal of Business Administration, 2019)
Abstract. PT Pertamina EP, a state-owned enterprise engaged in exploration and production of oil and gas in the upstream sector should optimize wells assets to achieve company’s target. Current wells data management in the company resulting multiple data versions. This situation potentially impact on the operation. In 2013, the Director stated that  as much as 20% of oil drilling undertaken since 2008 have failed, resulting a net loss of USD 300 million. Therefore, it is necessary to implement integrated wells management system. This research uses dispatcher report from 2014-2015 regarding wells data. The research methodology consists of several steps, started from problem finding, root cause analyses, system solution, and system design definition. The data are analyzed using Pareto as the basis for root cause. Furthermore six primary dimension of data quality from DAMABoK, CRT mapping and qualitative interview are used for solving the problem. The proposed system named MAPS assessed based on six data quality dimensions. The result shows that the system meet four out of six data quality dimensions. It requires improvement of the capabilities in the future to integrate the system into company's business processes to to synchronize the data for further decision making process.Keywords:  data quality, integrated management system, MAPS, root cause , wells